An investigation into the risk behavior of rice farmers in Lampung, Indonesia - Haryono, Dwi; Rosanti, Novi; Sari, Dewi Mulia; Wulandari, Riri; Sinambela, Ebenezer (International Journal of Innovative Research and Scientific Studies, 2025)
Examining the variables that affect production risks, as well as how Lampung rice farmers respond to those risks, is the goal of this study. The data utilized was primary data obtained from three districts in Lampung Province, specifically South Lampung, Pesawaran, and Pringsewu. The data collection was conducted over the months of October and November in the year 2023. The research sample involved 161 rice farmers as respondents. The analysis employed the Just and Pope model, utilizing multiple linear regression, as well as the Moscardi and de Janvry model, to ascertain the preferences of farmers. The research findings indicate that the variables of land area, seeds, urea fertilizer, insecticides, and labor outside the family are factors that increase the risk. Rice farmers, in general, exhibit risk aversion and have a high tolerance for danger. Production hazards can be managed by applying precision agriculture, diversifying farming practices, and utilizing agricultural insurance.